Politics of religious minoritisation and glocalisation: notes towards a study of religious networks of transnational - Joanildo Burity (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
This article offers a preliminary analytical framework for the study of one of the main forms of global expression of religious movements in the contemporary scenario and its specific impact on the public sphere: the involvement of networks of social and political activism at translocal, trasnational and global levels. This is done through the analysis of the relationship between religion and globalisation, with particular attention to Christian groups, stressing two sets of processes: first, the dynamics of visibility and latency within these experiences; and second, the convergence betweenprocesses of minoritisation and imbrication of local and global (which will be developed though the concept of glocalisation). The study will be conducted as a comparative analysis of existing networks between Brazil, Argentina and the United Kingdom.